2014
DOI: 10.1293/tox.2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic Changes of Colchicine Intoxication in Rats: Electrocardiographic, Histopathological and Blood Chemical Analysis

Abstract: The microtubule inhibitor colchicine is cardiotoxic and is suggested to impair impulse formation and conduction. However, little is known about the electrocardiographic (ECG) changes induced by colchicine in experimental animals and the detailed pathogenesis of its cardiotoxicity. Therefore, we analyzed cardiotoxicity in colchicine-treated rats using electrocardiographic, histopathological and blood-chemistry approaches. A telemetry device for transmitting ECG data was implanted into male Crl:CD(SD) rats, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…First, the relative increase in tubulin, the individual subunits of microtubules, in PAB ( Supplemental Figure S6 ) are less than what we observed in MCT rats [ 31 ], and there may be a threshold of microtubule remodeling needed for a pathological response. Second, it is possible that chronic colchicine treatment and microtubule depolymerization could have adverse effects on cardiac function as a previous manuscript showed high dose colchicine causes cardiac conduction abnormalities, however at much higher doses than we used [ 32 ]. While there are strong data linking microtubule remodeling to impaired cardiac contractility [ 33 , 34 , 35 ], perhaps the less prominent microtubule phenotype of PAB rats cannot be enhanced with colchicine because microtubule remodeling is not the driving force of this mild right ventricular dysfunction phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…First, the relative increase in tubulin, the individual subunits of microtubules, in PAB ( Supplemental Figure S6 ) are less than what we observed in MCT rats [ 31 ], and there may be a threshold of microtubule remodeling needed for a pathological response. Second, it is possible that chronic colchicine treatment and microtubule depolymerization could have adverse effects on cardiac function as a previous manuscript showed high dose colchicine causes cardiac conduction abnormalities, however at much higher doses than we used [ 32 ]. While there are strong data linking microtubule remodeling to impaired cardiac contractility [ 33 , 34 , 35 ], perhaps the less prominent microtubule phenotype of PAB rats cannot be enhanced with colchicine because microtubule remodeling is not the driving force of this mild right ventricular dysfunction phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 25 to 30 was targeted for 3 reasons: there were 3 groups in the analysis, to reduce effects of the heterogeneity with colchicine treatment, and to account for possible deaths during the experimental time frame. The dosing scheme was implemented as similar doses were shown to depolymerize the microtubule cytoskeleton in cardiomyocytes in rats23, 24 but less than doses that are associated with significant cardiotoxicity in rats 25. Four weeks after MCT injection was the end point of the study because a previous study had shown that time frame was associated with severe pulmonary hypertension 21…”
Section: Methodsmentioning
confidence: 99%
“…The study indicated that ephedrine isolated from Ephedra sinica Stapf could trigger a range of cardiovascular toxicities, including myocarditis, arrhythmias, myocardial infarction, cardiac arrest, heart failure, and sudden death ( Samenuk et al, 2002 ; Adamson et al, 2004 ; Naik and Freudenberger, 2004 ; Nyska et al, 2005 ). Colchicine derived from Colchicum autumnale has been proved to impair impulse formation and conduction ( Tochinai et al, 2014 ). Another study suggested that colchicine could directly damage cardiac endothelial cells to induce cardiotoxicity ( Mikaelian et al, 2010 ).…”
Section: Risk Compounds Of Cmm-induced Cardiotoxicitymentioning
confidence: 99%